1991
DOI: 10.1002/ana.410300416
|View full text |Cite
|
Sign up to set email alerts
|

Pleuropulmonary disease associated with dopamine agonist therapy

Abstract: Artificial dopamine agonists are widely employed for the treatment of idiopathic parkinsonism. Pleuropulmonary disease has previously been reported to occur with the use of bromocriptine and mesulergine. We report similar adverse effects induced by the newer agonists lisuride and cabergoline. All these agents are tetracyclic ergot derivatives. This suggests a causal link between ergot-derived dopamine agonists and pleuropulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 14 publications
2
33
0
4
Order By: Relevance
“…1. Pulmonary infiltrates in association with the pleural changes have been described in 16 of the 37 bromocriptine cases [17, 18, 22-26, 28, 29], in two ergotamine cases [36,39], and in one cabergoline case [33]. Round or oval-shaped opacities corresponding to foci of parenchymal atelectasis facing areas of thickened presumably immotile or retracted pleura (the so-called "folded lung" or "rounded atelectasis" have consistently been reported [4,9,12,32,34,36], and were also seen in two of our cases ( fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1. Pulmonary infiltrates in association with the pleural changes have been described in 16 of the 37 bromocriptine cases [17, 18, 22-26, 28, 29], in two ergotamine cases [36,39], and in one cabergoline case [33]. Round or oval-shaped opacities corresponding to foci of parenchymal atelectasis facing areas of thickened presumably immotile or retracted pleura (the so-called "folded lung" or "rounded atelectasis" have consistently been reported [4,9,12,32,34,36], and were also seen in two of our cases ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite structural differences, ergolines as a whole behave as substances fibrogenic to mesothelia, mediastinum and retroperitoneum. Whether fibrogenicity of ergolines is related to their core structure, to a common metabolite or to their serotoninergic activity [33] is currently unclear. In this connection, excess endogenous production of serotinin, as seen in the carcinoid syndrome, may also be associated with pleural fibrosis [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ESR and a low haemoglobin level are also present, together with general malaise and loss of weight [19]. Pleural effusion with various amounts of fluid may also occur [3,5,7,10,11,15,16,19].…”
Section: Discussionmentioning
confidence: 99%
“…In 1981, RINNE [2] reported that, out of 123 patients on long-term therapy with this drug, seven had developed pleuropulmonary reactions. Since then, to our knowledge, 30 cases of bromocriptine-induced adverse reactions in the lung and/or pleura have been reported in the literature [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Interestingly, ergot alkaloids other than bromocriptine can cause similar lesions in the chest [19].…”
mentioning
confidence: 99%